The jaw adductor muscle complex in teleostean fishes: evolution, homologies and revised nomenclature (osteichthyes: actinopterygii). - Aléssio Datovo (Public Library of Science (PLoS), 2013)
The infraclass Teleostei is a highly diversified group of bony fishes that encompasses 96% of all species of living fishes and almost half of extant vertebrates. Evolution of various morphological complexes in teleosts, particularly those involving soft anatomy, remains poorly understood. Notable among these problematic complexes is the adductor mandibulae, the muscle that provides the primary force for jaw adduction and mouth closure and whose architecture varies from a simple arrangement of two segments to an intricate complex of up to ten discrete subdivisions. The present study analyzed multiple morphological attributes of the adductor mandibulae in representatives of 53 of the 55 extant teleostean orders, as well as significant information from the literature in order to elucidate the homologies of the main subdivisions of this muscle. The traditional alphanumeric terminology applied to the four main divisions of the adductor mandibulae - A1, A2, A3, and Aω - patently fails to reflect homologous components of that muscle across the expanse of the Teleostei. Some features traditionally used as landmarks for identification of some divisions of the adductor mandibulae proved highly variable across the Teleostei; notably the insertion on the maxilla and the position of muscle components relative to the path of the ramus mandibularis trigeminus nerve. The evolutionary model of gain and loss of sections of the adductor mandibulae most commonly adopted under the alphanumeric system additionally proved ontogenetically incongruent and less parsimonious than a model of subdivision and coalescence of facial muscle sections. Results of the analysis demonstrate the impossibility of adapting the alphanumeric terminology so as to reflect homologous entities across the spectrum of teleosts. A new nomenclatural scheme is proposed in order to achieve congruence between homology and nomenclature of the adductor mandibulae components across the entire Teleostei.